Organic Waste Processing Based on A Circular Economy as an Environmentally Friendly Solution - Ni Putu Devi Sari Astiti; I Putu Krisna Tama Frandika; I Wayan Suwardika; I Made Rendy Adileo; I Putu Mahesa Aji Susena (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2025)
Circular economy-based waste management is an important approach to support environmental sustainability while improving community welfare. This study aims to analyze the organic waste management system in Tegal Tugu Village, Gianyar, by highlighting the implementation of a circular economy and its impacts on the environment and society. This study was conducted using qualitative methods and a case study approach, involving direct observation and descriptive analysis of the collected data. The results show that Tegal Tugu Village's organic waste is managed through sorting, composting, and fermentation. This process produces value-added products, such as organic fertilizer and biogas, which not only support sustainable agriculture but also reduce dependence on chemical fertilizers. Furthermore, the implementation of a circular economy in this village provides real economic benefits, including new business opportunities and job creation for the local community. However, some challenges must be overcome, such as the limited capacity of processing facilities and the level of community awareness that is not yet fully evenly distributed in sorting waste. Overall, this study contributes by offering a circular economy-based waste management model that is relevant to be applied in other areas. The implications of these findings include improving environmental quality, empowering communities, and developing a sustainable local economy. With consistent education and strengthening of infrastructure, Tegal Tugu Village can become a model for environmentally friendly and community-based organic waste management.